2021
DOI: 10.3390/catal11030303
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Performance of Immobilized Rhizopus oryzae Lipase on Coated Porous Polypropylene Support with Additives

Abstract: The immobilization of Rhizopus oryzae lipase (RoL) by hydrophobic adsorption on polypropylene supports with additives was investigated. Additives such as hen egg albumin, sodium caseinate and CAVAMAX® W6 were used to coat the support during immobilization where the immobilized RoL on coated support was compared to those of noncoated support. Following the immobilization, the catalytic activity of immobilized RoL was characterized based on different temperatures and pH. The immobilized RoL without additives sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…In the study developed by Sani et al [67], the lipase from Rhizopus oryzae was immobilized by physical adsorption on a polypropylene support with additive CAVAMAX ® W6 achieving an increase of 100% in relative activity after immobilization. According to the authors, the interactions between lipase and support were mostly hydrophobic, the hydropho-bic effect resulted in open conformation and interfacial activation of lipase during adsorption, leading to an improvement in the enzymatic activity after immobilization procedure.…”
Section: Immobilization Of a Japonicus Lipase Using Different Supportsmentioning
confidence: 99%
“…In the study developed by Sani et al [67], the lipase from Rhizopus oryzae was immobilized by physical adsorption on a polypropylene support with additive CAVAMAX ® W6 achieving an increase of 100% in relative activity after immobilization. According to the authors, the interactions between lipase and support were mostly hydrophobic, the hydropho-bic effect resulted in open conformation and interfacial activation of lipase during adsorption, leading to an improvement in the enzymatic activity after immobilization procedure.…”
Section: Immobilization Of a Japonicus Lipase Using Different Supportsmentioning
confidence: 99%
“…Palomo et al reported the hyperactivation of lipases from Mucor miehei, Candida rugosa, and Candida antarctica due to their adsorption on strongly hydrophobic materials such as octadecyl-sepabeads [10]. In addition, the preparation of active catalysts in the synthesis of ethyl oleate by immobilized Candida antarctica lipase B and Rhizopus oryzae lipase (RoL) on polypropylene was also reported [11,12]. Pencreac'h et al reported 100% conversions and improved selectivity (compared with the free enzyme) in the hydrolysis of p-nitrophenol acetate and p-nitrophenol palmitate in 2-propanol catalyzed by Pseudomonas cepacia lipase adsorbed on microporous polypropylene [13].…”
Section: Introductionmentioning
confidence: 99%